Astrocyte‐produced leukemia inhibitory factor expands the neural stem/progenitor pool following perinatal hypoxia–ischemia. Issue 12 (23rd September 2016) - Felling, Ryan J.; Covey, Matthew V.; Wolujewicz, Paul; Batish, Mona; Levison, Steven W.
Abstract : Brain injuries, such as cerebral hypoxia–ischemia (H‐I), induce a regenerative response from the neural stem/progenitors (NSPs) of the subventricular zone (SVZ); however, the mechanisms that regulate this expansion have not yet been fully elucidated. The Notch‐ Delta‐Serrate‐Lag2 (DSL) signaling pathway is considered essential for the maintenance of neural stem cells, but it is not known if it is necessary for the expansion of the NSPs subsequent to perinatal H‐I injury. Therefore, the aim of this study was to investigate whether this pathway contributes to NSP expansion in the SVZ after H‐I and, if so, to establish whether this pathway is directly induced by H‐I or regulated by paracrine factors. Here we report that Notch1 receptor induction and one of its ligands, Delta‐like 1, precedes NSP expansion after perinatal H‐I in P6 rat pups and that this increase occurs specifically in the most medial cell layers of the SVZ where the stem cells reside. Pharmacologically inhibiting Notch signaling in vivo diminished NSP expansion. With an in vitro model of H‐I, Notch1 was not induced directly by hypoxia, but was stimulated by soluble factors, specifically leukemia inhibitory factor, produced by astrocytes within the SVZ. These data confirm the importance both of the Notch‐DSL signaling pathway in the expansion of NSPs after H‐I and in the role of the support cells in their niche. They further support the body of evidence that indicates that leukemia inhibitory factor is a key injury‐induced cytokine that is stimulating the regenerative response of the NSPs. © 2016 Wiley Periodicals, Inc. Abstract : Juxtacrine signaling subsequent to neonatal hypoxia–ischemia doubles the numbers of neural stem cells (NSCs) in the subventricular zone. Hypoxia–ischemia directly activates astrocytes to produce leukemia inhibitory factor (LIF), which stimulates the NSCs to increase their levels of Notch1 receptor. Hypoxia–ischemia also induces the expression of the ligand, Delta‐like 1, that promotes symmetrical division of the NSCs.